Maternal Preeclampsia Is Associated With Reduced Adolescent Offspring Hip BMD in a UK Population‐Based Birth Cohort - Hannam, Kimberly (J Bone Miner Res, 2015)
A suboptimal intrauterine environment has been postulated to have adverse long‐term health effects, including an increased risk of osteoporosis. Because preeclampsia (PE) and to a lesser extent gestational hypertension (GH) are associated with impaired placental function, we postulated that these represent hitherto unrecognized risk factors for reduced bone mineral density (BMD) of the offspring. The objective of this study was to investigate if exposure to PE or GH in utero is associated with BMD of the offspring as measured in late adolescence. Mother‐offspring pairs from the UK population‐based cohort study, Avon Longitudinal Study of Parents and Children (ALSPAC), were investigated (n = 3088 with relevant data). Multivariable linear regression was used to examine associations between PE/GH and total body, spine, and total hip BMD at age 17 years. Of the 3088 mother‐offspring pairs, 2% (n = 60) of the mothers fulfilled criteria for PE and 14% (n = 416) for GH. In confounder‐adjusted analyses (ie, age of scan, gender, maternal factors, including BMI, offspring height, fat mass, and lean mass), PE was negatively associated with BMD at the hip (SD difference –0.30; 95%CI, –0.50 to –0.10). This association was not attenuated by further adjustment for gestational age and birth weight, which were hypothesized to be on the causal pathway. There was also weak evidence for a negative association between PE and total body BMD (SD difference –0.17; 95% CI, –0.36 to 0.02), whereas no relationship was evident at the spine (SD difference –0.11; 95% CI, –0.30 to 0.09). In contrast, a positive association of GH with offspring total body, hip, and spine BMD attenuated to the null with adjustment for confounders, in particular confounding via the maternal and offspring adiposity/size and the link between the two. Modest negative associations from exposure to PE, but not GH may represent a hitherto unrecognized risk factor for low BMD. Further exploration of the causal relationship of the in utero environment on subsequent offspring bone health is required. © 2015 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.